ASUHAN KEBIDANAN PADA Ny. “P” MASA KEHAMILAN, PERSALINAN, NIFAS, NEONATUS DAN KELUARGA BERENCANA DI WILAYAH KERJA UPT PUSKESMAS DLANGGU KABUPATEN MOJOKERTO - Mukarromatuz Zulfa; Dian Irawati, S.Keb.Bd.,M.Sc; Zulfa Rufaida, S.Keb.Bd.,M.Sc (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) is problem that must be solved by the Indonesian Nation. MMR in Indonesia on 2015 is 305 maternal deaths per 100,000 live births. While IMR in 2017 is 24 per 1000 live births. Midwifery care for Mrs. "P" G2P1A0 36-37 weeks of gestation in the work area of UPT Puskesmas Dlanggu. Midwifery care in continuity of care was carried out since pregnancy trimester III, childbirth, postpartum, neonates and family planning with SOAP expected to suppress MMR and IMR as small as possible. The results of midwifery care at pregnancy, mother complained that urinating frequently and under abdomen cramps. The membranes that rupture during labor are so cloudy that the mother must be referred. During the puerperal visit, the mother complained that her nipples were scuffed. Baby "J" is female born vaginally. At the second neonatal visit, baby had cold. Mothers chose 3 months KB injection. Based on midwifery care for Mrs. "P" is important to pay attention personal hygiene, resting, mothers should avoid herbs, sufficient her nutritional needs, breastfeed the baby with the right technique and often give her baby breast milk.